Responses of ecosystem water use efficiency to drought in the Lancang–Mekong River Basin - Luo, Xuan; Wang, Yinfei; Li, Yungang (Frontiers in Ecology and Evolution, 2023)
The ecosystem water use efficiency (WUE), a crucial indicator of how climate change will affect terrestrial ecosystems, depicts the coupling of the carbon gain and water loss in terrestrial ecosystems. In this study, the spatiotemporal variations in the WUE and its responses to drought in the Lancang–Mekong River Basin (LMRB) from 1982 to 2018 were investigated using the gross primary productivity (GPP) and evapotranspiration (ET) data acquired from the Global Land Surface Satellite (GLASS) products. The analyses revealed that: (1) the mean yearly WUE for the LMRB was 1.63 g C kg−1 H2O, with comparatively higher values in forests and warm temperate climatic types. The interaction of temperature and leaf area index was the main factor affecting the spatial distribution of WUE. The yearly WUE for the entire region exhibited a decreasing trend with a rate of −0.0009 g C kg −1 H2O·yr−1, and the spatially significantly decreasing area accounted for 41.67% of the total area. (2) The annual WUE was positively correlated with drought in the humid regions, accounting for 66.55% of the total area, while a negative relationship mainly occurred in the high-altitude cold region. (3) The ecosystem WUE lagged behind the drought by 3 months in most regions. The lag effect was more apparent in the grassland-dominated upstream region and the cropland-dominated Mekong Delta. (4) The resilience analysis revealed that the ecosystems in forests and temperate climate types were strongly resistant to drought, while the grassland and high-altitude regions with a dry and cold climate had relatively poor resilience. The results of this study shed light on how the WUE responds to drought across diverse land use types, climate types, and elevation gradients, uncovering fresh insights into the potential mechanisms behind the impact of drought on water and carbon cycles within ecosystems.